Cyberstalking Perpetration Among Young Adults: An Assessment of the Effects of Low Self-Control and Moral Disengagement. (November 2021) - Fissel, Erica R.; Fisher, Bonnie S.; Nedelec, Joseph L.
The current study sought to explain cyberstalking perpetration using low self-control and moral disengagement frameworks. Self-report survey data collected from a Mechanical Turk sample of 1, 500 young adults aged 18 to 25 years old revealed that approximately 22% of the sample had engaged in cyberstalking perpetration during their lifetime. Findings also generally supported the self-control and moral disengagement frameworks. Respondents with higher levels of low self-control were more likely to engage in cyberstalking perpetration, as were those respondents who had a higher moral disengagement score. The interaction between low self-control and moral disengagement, however, did not yield a significant effect.